Answer:
v= 17
Step-by-step explanation:
Start with the given equation.
19v – 18 = 16 + 17v
Move -18 to the other side, and swap it's sign.
19v = 16 + 18 + 17v
Move 17v to the other side and swap it's sign.
19v - 17v = 16 + 18
Combine like terms.
2v = 34
Divide by 2v.
v = 17
Answer:
see below for a graph
Step-by-step explanation:
Completing the square for x and y terms can help you put this in the standard form.
(x^2 +10x) +(y^2 +6y) = -18
(x^2 +10x +25) +(y^2 +6x +9) = -18 +25 +9 . . . . add square of half linear coefficient
(x +5)^2 +(y +3)^2 = 16 . . . . . . . circle centered at (-5, -3) with radius 4
Answer:
Step-by-step explanation:
(A) The difference between an ordinary differential equation and an initial value problem is that an initial value problem is a differential equation which has condition(s) for optimization, such as a given value of the function at some point in the domain.
(B) The difference between a particular solution and a general solution to an equation is that a particular solution is any specific figure that can satisfy the equation while a general solution is a statement that comprises all particular solutions of the equation.
(C) Example of a second order linear ODE:
M(t)Y"(t) + N(t)Y'(t) + O(t)Y(t) = K(t)
The equation will be homogeneous if K(t)=0 and heterogeneous if ![K(t)\neq 0](https://tex.z-dn.net/?f=K%28t%29%5Cneq%200)
Example of a second order nonlinear ODE:
![Y=-3K(Y){2}](https://tex.z-dn.net/?f=Y%3D-3K%28Y%29%7B2%7D)
(D) Example of a nonlinear fourth order ODE:
![K^4(x) - \beta f [x, k(x)] = 0](https://tex.z-dn.net/?f=K%5E4%28x%29%20-%20%5Cbeta%20f%20%5Bx%2C%20k%28x%29%5D%20%3D%200)
Answer:
correct answer is option B
Step-by-step explanation:
as we know equation of line
y = m x + c....................(1)
where c is the intercept
m is the slope
m = ![\dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
m = ![\dfrac{35-0}{1-0}](https://tex.z-dn.net/?f=%5Cdfrac%7B35-0%7D%7B1-0%7D)
m = 35
putting value of m in equation (1)
we get
y = 35 x + c
from the graph we can clearly see that line is passing through (0,0) hence
0 = 35 (0)x + c
c = 0
hence the equation of line comes out to be
y = 35 x
correct answer is option B
Coefficients are added together because they are like terms, this can be proven with the distributive property. For example, x(2x+x)=2x^2+x^2=3x^2.
The commutative property of addition and the associative property demonstrate this.
The word "commutative" comes from "commute" or "move around", so the Commutative Property<span> is the one that refers to moving values around.
</span>
The associative property<span> states that you can add or multiply regardless of how the numbers are grouped. </span>